A multiple slip plane model for crack-tip plasticity - Noronha, S; Roberts, S; Wilkinson, A (2000)
A single slip plane dislocation dynamics based model for the brittle to ductile transition has been extended to have multiple slip planes around the crack-tip. The crack-tip plastic behaviour is studied for a variety of dislocation source configurations. The results are presented for the case of iron. The effect of modelling the plastic-zone as a single slip plane and as an array of parallel slip planes are compared.